IMPLEMENTASI ETIKA BISNIS ISLAM PADA UMKM SUMBER BAROKAH DI DESA BUDUAN KECAMATAN SUBOH KABUPATEN SITUBONDO - Zainol Hasan; Risma Fahrul Amin; Fathorrosi Fathorrosi (Al-Idarah, 2023)
Not a few business people are still involved in usury transactions, reducing scales, committing gharar and fraud. With this fact, researchers are interested in examining whether UMKM Sumber Barokah whose owners are Muslim have implemented Islamic business ethics as the basis of their business activities. This study uses a qualitative descriptive method with a phenomenology and case study approach. The data sources used are primary and secondary data. Data collection techniques used are observation, interviews and documentation. Supporting factors for UMKM sumber barokah are: consumers know the product because it has good quality product, services can be done outside of working hours and have been known by people from outside the district and even outside the city. It also has employees who are skilled in making rengginang well. The inhibiting factors for UMKM sumber barokah are: the lack of capital that hindered business development, during the rainy season the production of rengginang is slightly hampered because the drying process still 100% depends on the intensity of sunlight, and in certain seasons it was difficult to get fish used as a product mix, and promotion on social media is still not optimal so that the product is not yet known by the wider society. UMKM Sumber Barokah in running their business has implemented Islamic business ethics by behaving well towards consumers, accentuating honesty, selling good quality products, being generous and building good relationships with consumers. Keyword: Islamic Business Ethics, UMKM (Micro, Small And Medium Enterprises), Islamic Economics